Noble Metals in Recent Developments of Heterogeneous Catalysts for CO2 Conversion Processes - Vieira, Luiz H.; Rasteiro, Letícia F. [UNESP]; Santana, Cássia S.; Catuzo, Gabriel L.; da Silva, Alisson H. M.; Assaf, José M.; Assaf, Elisabete M. (Wiley, 2023)
Following the advances in capture technologies, CO2 utilization associated with low-cost renewable H2 in catalytic hydrogenation is a promising strategy for reducing the carbon footprint of industrial processes by providing valuable chemicals and fuels. However, the scalability and economic viability of these processes will depend on the development of efficient catalysts. Noble metal-based catalysts have been extensively reported in the last few years as highly effective in promoting CO2 hydrogenation to various products. Although promising, the scarcity, high cost, and environmental impact of mining make it challenging to scale up these materials from bench to plant. Developing advanced synthesis and characterization methods is essential to control and understand active sites’ behavior during the reaction, providing high activity and durability. This review carefully summarizes the recently reported noble metal-based heterogeneous catalysts for thermocatalytic conversion of CO2 into methane, carbon monoxide, methanol, formic acid, higher alcohols, C2+ hydrocarbons, and syngas through dry reforming of CH4, to draw the state-of-the-art development in the field. Finally, we critically discuss the impact of these elements on catalyst properties, the challenges related to their implementation, and future research opportunities.
Keywords: alcohols; CO2 hydrogenation; hydrocarbons; noble metals; reverse water-gas shift